Metabolic signature and proteasome activity controls synovial migration of CDC42hiCD14+ cells in rheumatoid arthritis - Malmhäll-Bah, Eric; Andersson, Karin M.E.; Erlandsson, Malin C.; Silfverswärd, Sofia T.; Pullerits, Rille; Bokarewa, Maria I. (Frontiers in Immunology, 2023)
Objective: Activation of Rho-GTPases in macrophages causes inflammation and severe arthritis in mice. In this study, we explore if Rho-GTPases define the joint destination of pathogenic leukocytes, the mechanism by which they perpetuate rheumatoid arthritis (RA) and how JAK inhibition mitigates these effects.Methods: CD14 + cells of 136 RA patients were characterized by RNA-sequencing, and cytokine measurement to identify biological processes and transcriptional regulators specific for CDC42 hi CD14 + cells, which were summarized in a metabolic signature (MetSig). Effect of hypoxia, and IFN-γ signaling on the metabolic signature of CD14 + cells was assessed experimentally. To investigate its connection with joint inflammation, the signature was translated into the single cell characteristics of CDC42 hi synovial tissue macrophages. Sensitivity of MetSig to the RA disease activity and treatment effect was assessed experimentally and clinically.Results: CDC42 hi CD14 + cells carried MetSig of genes functional in the oxidative phosphorylation and proteasome-dependent cell remodeling, which correlated with the cytokine-rich migratory phenotype and antigen presenting capacity of these cells. Integration of CDC42 hi CD14 + and synovial macrophages marked with MetSig revealed the important role of the interferon-rich environment and immunoproteasome expression in homeostasis of these pathogenic macrophages. The CDC42 hi CD14 + cells were targeted by JAK-inhibitors and responded with downregulation of immunoproteasome and This is a provisional file, not the final typeset article MHC-II molecules, which disintegrated the immunological synapse, reduced cytokine production and alleviated arthritis.This study shows that the CDC42-related MetSig identifies the antigen-presenting CD14 + cells that migrate to joints to coordinate autoimmunity. Accumulation of CDC42 hi CD14 + cells disclose patients perceptive to JAKi treatment.